THE QUALITY AND HEALTH RISK ASSESSMENT OF POLYETHYLENE-PACKAGED TABLE WATER SUNLIGHT EXPOSED AND UNEXPOSED DURING STORAGE (FUDMA JOURNAL OF SCIENCES, 2025)
Exposure of sachet water to sunlight by vendors is a common practice in Nigeria which could affect its quality. In this study, 80 sachets of branded table water divided equally into group 1 (exposed to sunlight) and group 2 (unexposed to sunlight); were stored for 16 days. At four days interval, microbiological, physicochemical properties, minerals, and heavy metals concentration of the stored sachet water samples were determined using standard methods. There was reduction in total heterotrophic bacterial count (THBC), total coliform count (TCC), and total fungal count (TFC) of sachet water exposed to sunlight. The THBC, TCC, and TFC of all the samples ranged from 3.70-5.04, 0.00-3.95, 0.00-4.36 log10CFU/ml, respectively. Bacterial species isolated from the stored sachet water were resistant to most antibiotics. Non-microbiological properties of the stored sachet water were within the World Health Organization (WHO) permissible limits, with the exception of pH. The concentration of metals in the sachet water fluctuated during storage, whereas Cd and Pb was below detection limit. The non-microbiological properties of the stored sachet water monitored at intervals were significantly different (p
Keywords: Antimicrobial Resistance; Heavy Metals; Potable Water; Public Health; Waterborne Pathogens